RESPON PEMBERIAN PUPUK KOTORAN AYAM DAN KOMPOS LIMBAH KAYU PUTIH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata. Sturt) - Siti Rahminah; Andi Apriany Fatmawaty; Nuniek Hermita; Abdul Hasyim (Partner, 2023)
Sweet corn is a food crop that ranks third after wheat and rice. Corn production has decreased significantly while demand is quite high. Therefore, in this paper the author wants to examine the effect of providing chicken manure compost and eucalyptus waste on the growth and yield of sweet corn (Zea mays saccharata Sturt). The experimental design used was the Factorial RAK which consisted of two factors, namely chicken manure and eucalyptus waste compost. The results showed that the dose of chicken manure of 20 tons/ha given the best results in the vegetative phase of plant height (191.11 cm), generative phase 20 tons/ha gave the best results with cob weight without husks (214.10 grams). In the other generative phases, a dose of 15 tons/ha of chicken manure gave the best results on cob length without husk (30.02 cm). There was an interaction between chicken manure compost and eucalyptus waste. Key Words:  chicken manure, eucalyptus, fertilizer, sweet corn, waste compost.